Lactobacillus rhamnosus (LGG) regulates IL-10 signaling in the developing murine colon through upregulation of the IL-10R2 receptor subunit. - Julie Mirpuri; Ilya Sotnikov; Loren Myers; Timothy L Denning; Felix Yarovinsky; Charles A Parkos; Patricia W Denning; Nancy A Louis (PLoS ONE)
The intestinal microflora is critical for normal development, with aberrant colonization increasing the risk for necrotizing enterocolitis (NEC). In contrast, probiotic bacteria have been shown to decrease its incidence. Multiple pro- and anti-inflammatory cytokines have been identified as markers of intestinal inflammation, both in human patients with NEC and in models of immature intestine. Specifically, IL-10 signaling attenuates intestinal responses to gut dysbiosis, and disruption of this pathway exacerbates inflammation in murine models of NEC. However, the effects of probiotics on IL-10 and its signaling pathway, remain poorly defined. Real-time PCR profiling revealed developmental regulation of MIP-2, TNF-α, IL-12, IL-10 and the IL-10R2 subunit of the IL-10 receptor in immature murine colon, while the expression of IL-6 and IL-18 was independent of postnatal age. Enteral administration of the probiotic Lactobacillus rhamnosus GG (LGG) down-regulated the expression of TNF-α and MIP-2 and yet failed to alter IL-10 mRNA and protein expression. LGG did however induce mRNA expression of the IL-10R2 subunit of the IL-10 receptor. IL-10 receptor activation has been associated with signal transducer and activator of transcription (STAT) 3-dependent induction of members of the suppressors of cytokine signaling (SOCS) family. In 2 week-old mice, LGG also induced STAT3 phosphorylation, increased colonic expression of SOCS-3, and attenuated colonic production of MIP-2 and TNF-α. These LGG-dependent changes in phosphoSTAT3, SOCS3, MIP-2 and TNF-α were all inhibited by antibody-mediated blockade of the IL-10 receptor. Thus LGG decreased baseline proinflammatory cytokine expression in the developing colon through upregulation of IL-10 receptor-mediated signaling, most likely due to the combined induction of phospho-STAT3 and SOCS3. Furthermore, LGG-dependent increases in IL-10R2 were associated with reductions in TNF-α, MIP-2 and disease severity in a murine model of intestinal injury in the immature colon.